As frações contínuas e os números metálicos - Araújo, José Júnior Veloso de (2015)
The familyofmetallicmeanswasintroducedbytheArgentinemathematicsVera Spinadel, in1994.Themetallicmeansareunknown,exceptfortheGoldenMean. However,othermetallicmeansalsohavepropertiesandimportantapplications.The ContinuedFractionsenableanotherwaytorepresentthesenumbers,whichareir- rational.